Seasons of moon and flame : the wild dreamer's epic journey of becoming - Dulsky, Danielle, 1980- (New World Library, 2020)
"Seasons of Moon and Flame is an introductory guide to neo-paganism and feminist spirituality that invites readers to live a "year of the wild" by aligning themselves with the cycles of the "thirteen seasons" of the moon. Discusses daily ceremonies, full moon rituals, poetry, and practical magick"--